Ferroptosis: Final destination for cancer?. (25th February 2020) - Ye, Zeng; Liu, Wensheng; Zhuo, Qifeng; Hu, Qiangsheng; Liu, Mengqi; Sun, Qiqing; Zhang, Zheng; Fan, Guixiong; Xu, Wenyan; Ji, Shunrong; Yu, Xianjun; Qin, Yi; et al.
Abstract: Ferroptosis is a recently defined, non‐apoptotic, regulated cell death (RCD) process that comprises abnormal metabolism of cellular lipid oxides catalysed by iron ions or iron‐containing enzymes. In this process, a variety of inducers destroy the cell redox balance and produce a large number of lipid peroxidation products, eventually triggering cell death. However, in terms of morphology, biochemistry and genetics, ferroptosis is quite different from apoptosis, necrosis, autophagy‐dependent cell death and other RCD processes. A growing number of studies suggest that the relationship between ferroptosis and cancer is extremely complicated and that ferroptosis promises to be a novel approach for the cancer treatment. This article primarily focuses on the mechanism of ferroptosis and discusses the potential application of ferroptosis in cancer therapy.